Effectiveness of Stimulation of Acupoint KI 1 by Artemisia vulgaris (Moxa) for the Treatment of Essential Hypertension: A Systematic Review of Randomized Controlled Trials. (13th March 2014) - Yang, Xiaochen; Xiong, Xingjiang; Yang, Guoyan; Wang, Jie
Abstract : Objective . A systematic review of randomized controlled trials has been performed to assess the effectiveness of stimulation of acupoint KI 1 by Artemisia vulgaris (the Japanese name is moxa) to lower blood pressure compared to antihypertensive drugs. Methods and Findings . Articles published from 1980 to August 2013 in databases of CENTRAL, Pubmed, CBM, CNKI, VIP, and online clinical trial registry websites were searched. Studies included were randomized controlled trials (RCTs); moxibustion-type intervention on KI 1 compared with antihypertensive drugs; meta-analysis showed superior effects of moxibustion plus antihypertensive drugs on systolic blood pressure (WMD: −4.91 [−7.54, −2.28]; P = 0.0003 ) but no superior effects on diastolic blood pressure (WMD: −6.38 [−17.17, 4.41]; P = 0.25 ). Conclusions . Our systematic review of the current literature shows a beneficial effect of using moxibustion interventions on KI 1 to lower blood pressure compared to antihypertensive drugs. However, the results are influenced by the existing differences in design of the current trials.